Analisis Viktimisasi Struktural Terhadap Korban Perdagangan Perempuan Di Kota Pekanbaru (Studi Kasus Dl, Ee Dan Ya) - M Zulherawan; Sukardi (SISI LAIN REALITA, 2021)
This study aims to determine the correlation between area mapping and the pattern of crime prevention (preventive efforts) used by the Ujung Batu Police. The method used is a qualitative method with a descriptive type of research by conducting interviews with key informants and informants who are in accordance with the research objectives and have relevant knowledge and information about the main problems in this study. Based on the results of the research, the mapping of crime-prone areas is very helpful for the police in carrying out preventive efforts, namely in preventing crimes that occur in Ujung Batu District, because from this mapping we can know which areas are the most vulnerable and what crimes dominate in the area. that. There are several steps taken by the Ujung Batu Sector Police in preventing the emergence of factors that cause crime in the legal domain of the Ujung Batu Police, including conducting patrols and adding police personnel, conducting village visits, and holding night patrols. The efforts made by the Ujung Batu Sector Police are carried out in a way that focuses on eliminating and minimizing the factors that cause crime.